Complication Following percutaneous coronary intervention via the femoral artery Experience in lraqi center for the Heart Disease and lbn Al-Bitar Hospital for cardiac surgery. - Majeed, Salah M.; Bahjet Al Saffar, Hilal; AL- Marayati, Amal N. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Vascular complications have been recognized as an important factor in morbidity after diagnostic and percutaneous coronary interventions.Objectives: This study sought to evaluate vascular complications after diagnostic coronary angiography and percutaneous coronary intervention (PCI) from the common femoral artery.Patients and methods: This prospective cohort study was carried out over a year period, from February 2008 till January 2009, at the Iraqi Center for the Heart Disease and Ibn Al-Bitar Hospital for Cardiac Surgery. A total number of 2400 patients underwent 3600 procedures, diagnostic coronary angiography (2196) and PCI(1404) via their common femoral arteries were included in this study.Result: A total 407(11.3%) patients developed different vascular complications (retroperitoneal hematoma, loss of distal pulse, arterial perforation each of them 0.03%, bruises 8.9%, pseudoaneurysm 0.69%, AV fistula 0.03%, hematoma ≥10cm 0.3% and